A Review of Digital Economy Enabling the Transformation and Upgrading of China’s Manufacturing Industry : Bibliometric Analysis Based on CiteSpace - Peng, Chun; Zhang, Shuangyang (International Journal of Global Economics and Management, 2024)
This paper examines the relevant literature on the transformation and upgrading of China's manufacturing industry enabled by digital economy, using Citespace visualization software. The analysis shows that the hotspots of research focus on digitalization, artificial intelligence, and industrial transformation. The research emphasizes digital economy and manufacturing digitalization, manufacturing innovation, allocation of manufacturing resources, and high-quality development of the manufacturing industry. Future research can focus on practical case studies and complete system evaluations to further enrich our understanding of these topics.